2021
DOI: 10.1177/14604582211021471
|View full text |Cite
|
Sign up to set email alerts
|

Toward a machine learning model for a primary diagnosis of Guillain-Barré syndrome subtypes

Abstract: Guillain-Barré Syndrome (GBS) is a neurological disorder affecting people of any age and sex, mainly damaging the peripheral nervous system. GBS is divided into several subtypes, in which only four are the most common, demanding different treatments. Identifying the subtype is an expensive and time-consuming task. Early GBS detection is crucial to save the patient’s life and not aggravate the disease. This work aims to provide a primary screening tool for GBS subtypes fast and efficiently without complementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Nevertheless, patient 1 initially experienced diplopia and limb numbness, followed by bilateral facial paralysis and manifestations of encephalopathy (mental disorder, ataxia, and pyramidal tract damage), and finally had obvious residual neurological sequelae. This patient simultaneously presented with the characteristic clinical features of both MSF ( 18 , 19 ) and BBE ( 20 ), which has rarely been reported in patients with anti-sulfatide antibody-related GBS. MFS is considered the most common variant of GBS and is characterized by the medical triad of ophthalmoplegia, ataxia, and areflexia ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Nevertheless, patient 1 initially experienced diplopia and limb numbness, followed by bilateral facial paralysis and manifestations of encephalopathy (mental disorder, ataxia, and pyramidal tract damage), and finally had obvious residual neurological sequelae. This patient simultaneously presented with the characteristic clinical features of both MSF ( 18 , 19 ) and BBE ( 20 ), which has rarely been reported in patients with anti-sulfatide antibody-related GBS. MFS is considered the most common variant of GBS and is characterized by the medical triad of ophthalmoplegia, ataxia, and areflexia ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 69%
“…This patient simultaneously presented with the characteristic clinical features of both MSF ( 18 , 19 ) and BBE ( 20 ), which has rarely been reported in patients with anti-sulfatide antibody-related GBS. MFS is considered the most common variant of GBS and is characterized by the medical triad of ophthalmoplegia, ataxia, and areflexia ( 18 , 19 ). BBE is characterized by the medical triad of ophthalmoplegia, ataxia, and encephalopathy ( 20 ).…”
Section: Discussionmentioning
confidence: 69%
“…In the present study, the clinical symptoms of GBS in EAN rats were observably improved by celastrol. GBS primarily damages the peripheral nervous system (Alarcón-Narváez et al 2021). This study showed that celastrol mitigated the pathological damage of GBS in EAN rats.…”
Section: Discussionmentioning
confidence: 99%
“…Alarcón-Narváez et al [15], developed a primary screening tool for the identification of GBS subtypes from clinical variables collected in consultation, without resorting to additional invasive methods. Through experiments involving four classifiers, five filters for feature selection, and six wrappers, along with the oneversus-all (OvA) classification technique, a dataset consisting of 129 patient records from Mexico and 26 key clinical variables was evaluated.…”
Section: Review Literaturementioning
confidence: 99%